Game Mobile Makhsif Makhroj dan Sifat dengan Huruf Hijaiyah Menggunakan Visual Audio - Mubarok, Muhammad Syauqi; Fatimah, Dini Destiani Siti; Irpan, Nurul (Institut Teknologi Garut, 2025)
One of the obligations of a Muslim is to read the Qur'an correctly, therefore it is important to learn how to read the Qur'an since childhood. Based on research by the Ministry of Religious Affairs and Nuonline, an article was released that randomized research of approximately 10 thousand Muslims in 32 provinces in Indonesia found that 38.49% did not have Quran literacy. In an effort to reduce this problem, it is necessary to diversify the delivery of learning to read the Qur'an by utilizing information technology such as Mobile-based Games. Based on these reasons, the purpose of this research is to design a game to help learning Makhroj and Sifat. The game development uses the Multimedia Development Life Cycle (MDLC) method. The method has 5 stages, namely, Concept, Design, Material Collecting, Assembly, and Distribution. The Alpha test results show that the game has successfully performed all the functions tested. The value of the Beta test results from seven questions given to 15 respondents is 89% which states that users are ‘Very Satisfied’. Therefore, it is hoped that this game can help children related to good and correct reading of makhroj.